Thermomate: bringing a new concept in portable beverage temperature solutions to the market - Shamsul Arif, Nur Athirah; Zulkifly, Nur Zeety Nabila; Ahmad Rizal, Nur Emiera Batrisyia; Rabuzi, Nur Afrina Amirah; Solehan, Nur Tasneem Umairah; Mohammad, Noorita (Universiti Teknologi MARA, Negeri Sembilan, 2025)
In the fast-paced and convenience-driven environment of college life, students often face difficulties in accessing beverages at their desired temperatures due to limited facilities in dormitories and academic buildings. Thermomate is a conceptual solution that addresses this problem by offering a portable, smart tumbler capable of both heating and cooling drinks. This study explores the idea development of Thermomate using a conceptual methodology, based on logical reasoning, creativity, and existing technologies such as thermoelectric modules. Through analysis of student needs and limitations of current solutions, the proposed tumbler stands out for its practicality, portability, and potential to support hydration and well-being among students. While still in its ideation phase, Thermomate presents a compelling opportunity for future product development and commercialization aimed at improving daily convenience and health habits for students and other users in mobile lifestyles.